ANALYSIS OF THE IMPACT OF SOCIAL SUPPORT ON DEPRESSION AMONG UNIVERSITY STUDENTS - suwolo, anggun eka putri; Murdhiono, Wahyu Rochdiat; Khasanah, Nur; Riska, Herliana (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Depression is one of the mental health disorders that is increasingly experienced by university students. Social support is believed to help reduce the level of depression through providing emotional, informational, and instrumental assistance. This study aims to analyze the relationship between social support and depression in university students in the Special Region of Yogyakarta (DIY). This research design is quantitative with a cross-sectional approach, involving 596 students from 11 universities selected by proportional random sampling. The research instruments included the Oslo Social Support Scale (OSS-3) to measure social support and the Depression Anxiety Stress Scale (DASS-21) to measure depression levels. Data analysis was conducted using the Spearman Test. The results showed that students' social support scores were included in high social support (mean=9.73), while depression scores were in the low category (mean=4.78). Statistical analysis showed a weak but significant positive relationship between social support and depression (r=-0.221; p=0.000). The regression test shows that if the social support score decreases by 2 points, the depression score will increase by 1 point. It is hoped that the results of this study can be the basis for intervention in increasing social support to prevent depression in college students.